19. EVALUATION OF THE EFFECT OF ELECTROACUPUNCTURE, ACUPRESSURE MASSAGE COMBINED WITH WILLIAMS EXERCISES IN THE TREATMENT OF SCIATICA DUE TO LUMBAR SPINE DEGENERATION (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of treatment of sciatica due to lumbar spine degeneration using electroacupuncture, acupressure massage combined with Williams exercises.Methods: A pre-post clinical intervention study was conducted on 60 patients. Patients received 14 days of combined electroacupuncture, acupressure massage and Williams exercises treatment. Key evaluation indices included the VAS pain scale, Schober test, Lasègue test, and overall treatment effectiveness.Results: After 14 days of treatment, VAS, Schober, and Lasègue indices all showed significant improvement compared to baseline (p < 0.05). The rate of patients achieving overall treatment effectiveness of fair or better was 80% (53.3% good and 26.7% fair).Conclusions: The combined regimen of electroacupuncture, acupressure massage and Williams exercises showed positive effects after 14 days in treating sciatica due to lumbar spine degeneration, significantly improving clinical symptoms.
Keywords: Sciatica; lumbar spine degeneration; electroacupuncture; acupressure massage; Williams exercises; traditional medicine.